Kaidah Pengulangan Lafaz dalam al-Qur’an: Studi Analisis QS. an-Naml[27]: 60-64 - Wulandari, Dewi; Yusuf, Moh.Asror; Marhumah, Qoidatul (Institut Agama Islam Negeri Kediri, 2023)
This article aims to examine the meaning of the repetition of phrases (tikrār) found in QS. an-Naml [27]: 60-64. These verses briefly discuss faith in Allah as a very important teaching and a core aspect of human life. Therefore, it is interesting to explore the meaning of the repetition of phrases implied in the verses that discuss this creed. Some research questions to be answered are: first, what is the meaning of the repetition of phrases in QS. an-Naml [27]: 60-64?; second, what wisdom is contained in this repetition of phrases? The research method used in this study is descriptive-analytical method. Based on the research findings, it is concluded that the meaning of the repetition of phrases in QS. an-Naml [27]: 60-64 is a